PENGARUH ETIKA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SIBOLGA SAMBAS - Tuti Alawiyah Tanjung; Kaharuddin; Rosmita Ambarita (CV. ALIM'SPUBLISHING, 2023)
The formulation of the problem in this study is whether work ethics and work motivation have a positive and significant effect on employee performance at the Sibolga Sambas District Office. This study aims to determine the effect of work ethics and work motivation on employee performance at the Sibolga Sambas District Office. The sample in this study were all employees of Sibolga Sambas District, totaling 87 (eighty seven) people. The data analysis technique in this study is Multiple Linear Regression. The results of this study indicate: work ethics partially has a positive and significant effect on employee performance; Work motivation partially has a positive and significant effect on employee performance; Work ethics and work motivation partially have a positive and significant effect on employee performance.